2018
DOI: 10.1364/boe.9.003167
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal detection of thalassemia by cell-free fetal DNA (cffDNA) in maternal plasma using surface enhanced Raman spectroscopy combined with PCR

Abstract: Thalassemias are widely occurring genetic hemoglobin disorders; patients with severe thalassemia often require regular blood transfusions for survival. Prenatal detection of thalassemia is currently invasive and carries the risk of miscarriage and infection. A polymerase chain reaction (PCR)-based surface enhanced Raman spectroscopy (SERS) technique was investigated in this paper for the purpose of detecting prenatal α-thalassemia Southeast Asian (SEA) type deletion using maternal plasma. Couples with the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The cffDNA consists of a shorter sequence than maternal DNA. Therefore, an amplification and few steps are required for the identification and is proceeded with PCR and HRM analysis to detect mutation in the fetal DNA 40 .…”
Section: Gap-polymerase Chain Reaction (Gap-pcr)mentioning
confidence: 99%
“…The cffDNA consists of a shorter sequence than maternal DNA. Therefore, an amplification and few steps are required for the identification and is proceeded with PCR and HRM analysis to detect mutation in the fetal DNA 40 .…”
Section: Gap-polymerase Chain Reaction (Gap-pcr)mentioning
confidence: 99%
“…Although fetal cffDNA is abundant and readily available in maternal plasma, prenatal screening based on cffDNA has been used to diagnose trisomy (13,18,21) and other genetic diseases (e.g., thalassemia). However, cffDNA-based diagnosis has some disadvantages: (1) due to cffDNA fragmentation, it is difficult to diagnose chromosomal mosaicism, duplication, deletion, and other abnormalities; (2) cffDNA-based diagnosis requires deep sequencing with high cost and low sensitivity [6][7][8]. Compared with the former, fetal cells contain complete cell structure and a full set of genomic information, and, with the progress of single-cell genomic detection technology, research results show that fetal cells have been able to analyze single-cell DNA accurately and specifically [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al, have applied this PCR-SERS method for multiplex detection of mutations associated with lung cancer, colorectal cancer and thalassemia respectively, substituting magnetic bead separation for PCR purification. 6,7,8 Furthermore, Wee et al, reported a PCR-SERS method for multiplex detection of melanoma associated mutations in circulating tumour DNA, omitting sperminemediated aggregation in favour of enrichment and SERS detection directly on the surface of magnetic beads. 9 This was achieved using a biotinylated reverse primer for magnetic bead capture, and a forward primer modified with an internal spacer and 5' overhang for direct hybridisation to dye-coded and DNA functionalised nanoparticles.…”
Section: Introductionmentioning
confidence: 99%